Epidemiological and Clinical Characteristics of Egyptian Patients with Hepatocellular Carcinoma: A Single Center Study - El-Assal, Mohamed; Al Hassanin, Suzan A; Hussein, Ahmed M (International Journal of Medical and Health Sciences Research, 2015)
Background: Hepatocellular carcinoma is a common malignancy, which usually develops on top of cirrhosis of viral origin; it is responsible for more than one million deaths worldwide per year. Aim: This study was conducted to identify the epidemiological and clinical characteristics of HCC patients attended Menofia oncology unit in the duration from 2003-2012, Egypt. Methodology: A retrospective analysis of records of 1500 HCC patients attended the Menofia oncology unit .The results: Of the 1500 studied HCC patients, 74.4% (1116) were male, and mean age was 54.98 years. HCV, HBV infection was reported to be 69.8 %, 17.2%, respectively, and 18.6 % were positive for Bilharziasis. Cirrhosis was present in (58.93%) of patients and was classified as Child-A (64.47%), Child-B (26.53 %) and Child-C (9 %). Hepatocellular carcinoma was multifocal/ diffuse in (51.26 %) of patients. 59.8% of patients were presented with metastatic disease. As regard to therapy; (59.6 %) of patients received palliative treatment, meanwhile about 28.1%, 12.3 % underwent other lines of treatment, no treatment, respectively. Conclusion: According to the results of this study, we concluded that most of HCC patients presented at Menofia oncology unit were of advanced stage and poor survival. More effort is needed to discover early HCC cases with high risk factors.